Comparison Of Front - And Back - Junctions Monocrystalline Silicon Solar Cell - Bagudo, Ibrahim Muhammad (2008)
This thesis undertakes fabrication, characterization and optimization of front and back junction solar cells. As part of our effort on cost reduction strategy, a simple technologies of conventional furnace processing (CFP) and rapid thermal processing (RTP) has been compared. Tesis ini menjalankan fabrikasi, pencirian dan pengoptimuman sel-sel suria persimpangan depan dan belakang. Sebagai sebahagian usaha kami iaitu strategi pengurangan kos, satu teknologi mudah pemprosesan relau konvensional (CFP) dan pemprosesan terma yang pesat (RTP) telah dibandingkan